Combination Therapy in Pulmonary Arterial Hypertension—Targeting the Nitric Oxide and Prostacyclin Pathways. (September 2021) - Mandras, Stacy; Kovacs, Gabor; Olschewski, Horst; Broderick, Meredith; Nelsen, Andrew; Shen, Eric; Champion, Hunter
Pulmonary arterial hypertension (PAH) is a chronic and progressive disorder characterized by vascular remodeling of the small pulmonary arteries, resulting in elevated pulmonary vascular resistance and ultimately, right ventricular failure. Expanded understanding of PAH pathophysiology as it pertains to the nitric oxide (NO), prostacyclin (prostaglandin I2 ) (PGI2 ) and endothelin-1 pathways has led to recent advancements in targeted drug development and substantial improvements in morbidity and mortality. There are currently several classes of drugs available to target these pathways including phosphodiesterase-5 inhibitors (PDE5i), soluble guanylate cyclase (sGC) stimulators, prostacyclin class agents and endothelin receptor antagonists (ERAs). Combination therapy in PAH, either upfront or sequentially, has become a widely adopted treatment strategy, allowing for simultaneous targeting of more than one of these signaling pathways implicated in disease progression. Much of the current treatment landscape has focused on initial combination therapy with ambrisentan and tadalafil, an ERA and PDE5I respectively, following results of the AMBITION study demonstrating combination to be superior to either agent alone as upfront therapy. Consequently, clinicians often consider combination therapy with other drugs and drug classes, as deemed clinically appropriate, for patients with PAH. An alternative regimen that targets the NO and PGI2 pathways has been adopted by some clinicians as an effective and sometimes preferred therapeutic combination for PAH. Although there is a paucity of prospective data, preclinical data and results from secondary data analysis of clinical studies targeting these pathways may provide novel insights into this alternative combination as a reasonable, and sometimes preferred, alternative approach to combination therapy in PAH. This review of preclinical and clinical data will discuss the current understanding of combination therapy that simultaneously targets the NO and PGI2 signaling pathways, highlighting the clinical advantages and theoretical biochemical interplay of these agents.